Gross heating value of various shade-trees wood in coffee plantation in Costa Rica and its relation with extractives and specific gravity - Roger Moya; Róger Bonilla; Carlos Zelada Fonseca (Indonesian Coffee and Cocoa Research Institute, 2018)
Shade-trees with energy use in coffee plantations are an important alternative to increase profitability in groforestry systems. The aim of this study was to investigate gross calorific value (GCV) of 15 shade-tree species in coffee plantations in Costa Rica. The relationships between specific gravity and extractives content on GCV was evaluated. The results revealed that GCV varied from 15.9 to 21.9 MJ kg-1 for sapwood, and from 15.3 to 21.9 MJ kg-1 for heartwood. No consistency was observed regarding to relation of type of wood (sapwood orheartwood) and GCV. The highest GCV value was found in Pinus caribaea for sapwood and heartwood. However Cupressus lusitanica, presented high GCV in sapwood too. The lowest values were found in Schizolobium parahyba in sapwood and Zygia longifolia and Eucalyptus globulus in heartwood. Carbon content (C) and carbon/nitrogen ratio (C/N ratio) and extractives in sodium hydroxide and dichloromethane were correlated with GCV in sapwood and heartwood. Meanwhile extractives in hot water were correlated in heartwood, and nitrogen content (N) and extractives in cool water were too correlated in sapwood.